(untitled) (Bangladesh Journal of Pharmacology, 2025)
This study investigates the diabetic wound healing potential of M. pendens using an in vivo diabetic animal model and molecular docking targeting MMP, EGF, and FGF pathways. Ethyl acetate hydrogel formulations (0.05%, 0.10%, and 0.15%) were tested over 14 days, with wound closure measured using ImageJ. The fraction contained 91.5 mg QE/g of flavonoids. Docking analysis showed strong binding affinities of quercetin, cholesta-22,24-dien-5-ol, and procyanidin B1 to MMP, EGFR, and FGFR (−8.4 to −10.2 kcal/mol). By day 14, the negative control group showed 30-40% wound closure, while tetrachlorodecaoxide reached 80% (p<0.01). The 0.05% hydrogel achieved 85% closure (p<0.05), and the 0.10% hydrogel showed complete healing (100%, p<0.001). The 0.15% hydrogel was less effective than 0.10%, with significant differences between days 7 and 14 (p<0.05). These findings suggest that M. pendens hydrogel may aid diabetic wound healing through molecular pathway modulation.